Safety evaluation of airworthiness requirement of bird-strike on aeroplane. (August 2019) - Cai, Jing; Bao, Han; Zuo, Hongfu; Huang, Yan
Abstract: Bird-strike is a potentially serious and damaging event, and the environment of bird flock and the design of anti-bird-strike have a significant effect on the probability and criticality of bird-strike. Therefore, the relationship among the environment of bird flock, the design of anti-bird-strike and risk requirement is illustrated firstly from the view of airworthiness. Secondly, in order to describe the characteristic of bird flock, the distribution of impact energy of bird-strike under the environment of bird flock in China are obtained and verified with twofold two-parameter mixed Weibull model. Finally, the quantitative relationship between risk requirement and sustainable bird-strike weight are determined to evaluate the airworthiness requirement of bird-strike. As an example, the existing airworthiness clause of bird-strike for the vertical stabilizer is evaluated. The proposed safety evaluation method in this work not only can help revise the airworthiness clauses of bird-strike based on a special bird flock environment, but also guide the design of anti-bird-strike. Highlights: The first study to build the distribution of impact energy of bird-strike under the environment of bird flock in China. The first study to build the quantitative relationship among bird flock, design of anti-bird-strike and risk requirement.